2021
DOI: 10.1155/2021/1567017
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibiofilm Effect of Thymol and Piperine in Combination with Aminoglycosides Antibiotics against Four Salmonella enterica Serovars

Abstract: Biofilms related to human infection have high levels of pathogenicity due to their resistance to antimicrobial agents. The discovery of antibiofilm agents is necessary. One approach to overcome this problem is the use of antibiotics agents’ combination. This study aimed to determine the efficacy of the combination of natural products thymol and piperine with three aminoglycosides antibiotics, amikacin, kanamycin, and streptomycin against biofilm-forming Salmonella enterica. The microtiter plate assay method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…In another study, thymol significantly inhibited 88% of methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation at 100 μg/ mL, reduced the surface adherence of MRSA, and enhanced the antibacterial and biofilm eradication efficiency of rifampicin against MRSA [9]. In addition, our recent studies reported a synergistic antibiofilm effect between thymol and aminoglycosides against K. pneumoniae and Salmonella enterica biofilms [10,11].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, thymol significantly inhibited 88% of methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation at 100 μg/ mL, reduced the surface adherence of MRSA, and enhanced the antibacterial and biofilm eradication efficiency of rifampicin against MRSA [9]. In addition, our recent studies reported a synergistic antibiofilm effect between thymol and aminoglycosides against K. pneumoniae and Salmonella enterica biofilms [10,11].…”
Section: Introductionmentioning
confidence: 94%
“…In another study, thymol significantly inhibited 88% of methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation at 100 μ g/mL, reduced the surface adherence of MRSA, and enhanced the antibacterial and biofilm eradication efficiency of rifampicin against MRSA [ 9 ]. In addition, our recent studies reported a synergistic antibiofilm effect between thymol and aminoglycosides against K. pneumoniae and Salmonella enterica biofilms [ 10 , 11 ]. The association of thymol with antibiotics showed a strong synergistic effect both in the inhibition of biofilm formation and the destruction of the preformed biofilm of K. pneumoniae , with the minimum biofilm inhibitory concentration (MBIC) and the minimum biofilm eradication concentration (MBEC) values of streptomycin being reduced by 16- to 64-fold [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effect of curcumin and piperine was confirmed by the results in this study. It is demonstrated that curcumin and piperine can inhibit bacteria by targeting the bacterial cell membrane, cell wall, protein, DNA, and/or by inhibiting bacterial growth through the quorum sensing (QS) system ( 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of plant extracts was characterized as bactericidal (MBC/MIC ≤4) or bacteriostatic (MBC/MIC <4) [ 33 ]. Additionally, the antifungal activity of plant extracts was considered fungicidal when MFC/MIC ≤4 and fungistatic when MFC/MIC >4 [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) of the extracts were determined by the broth microdilution Immunomodulatory [20] Tannins [21] A. manniana (Cyatheaceae) 25694/ HNC Leaves, seeds, Stembark Filariasis [22] Backache [23] Antioxidant [24] Flavonoids, quinones, tannins, terpenoids, and steroids [ The antibacterial activity of plant extracts was characterized as bactericidal (MBC/MIC ≤4) or bacteriostatic (MBC/MIC <4) [33]. Additionally, the antifungal activity of plant extracts was considered fungicidal when MFC/MIC ≤4 and fungistatic when MFC/MIC >4 [34].…”
Section: Antimicrobial Activitymentioning
confidence: 99%